Archive Management System to Support Orderly Administration at the National Narcotics Agency of Central Java Province - Anita Febriana; Tri Yuniningsih; Ika Riswanti Putranti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The research with the title "Archive Management System to Support Orderly Administration in the National Narcotics Agency of Central Java Province" aims to describe in depth the archive management system carried out in the organization and evaluate the obstacles faced in archive management in order to support orderly administration. The research uses a qualitative design through a case study approach with observation, interviews, and documentation as data collection methods. The data analysis technique uses data reduction, data presentation, and drawing conclusions. This research uses source and method triangulation. The results showed that the National Narcotics Agency of Central Java Province in managing archives still uses a manual system. Lack of facilities and infrastructure to support archive management. There is no awareness from employees in managing archives. There is no budget allocation for archive management activities. The archive management system is not maximized and needs to be paid attention to by the relevant leadership so that archive management can be better organized and effective in order to support administration at the National Narcotics Agency of Central Java Province.